The blended learning book : best practices, proven methodologies, and lessons learned - Bersin, Josh, 1956- (San Francisco, CA : Pfeiffer, 2004)
"A comprehensive look at the most discussed trend in training, The Blended Learning Book describes each step in defining, budgeting, building, managing, and measuring blended learning programs. With the accompanying website, learning professionals will be able to stay current on the emerging trends and future directions of blended learning."--Jacket.
Introduction -- Chap. 1. How did we get here? The history of blended learning -- Chap. 2. The business of blended learning -- Chap. 3. Blended learning concepts -- Chap. 4. Proven blended learning models -- Chap. 5. Eight criteria for selecting the blending model -- Chap. 6. Developing the budget -- Chap. 7. Media selection : the right blend -- Chap. 8. Content development -- Chap. 9. Learning technology and infrastructure -- Chap. 10. Program management : launch, rollout, support -- Moving forward -- Appendices.
Includes bibliographical references and index.
Keywords: Employees -- Training of; Employees -- Training of -- Computer-assisted instruction; Internet in education; Computer-assisted instruction; Blended learning